Efektivitas Layanan Bimbingan Kelompok Melalui Diskusi Kelompok Dalam Meningkatkan Kemampuan Mengelola Emosi Remaja - Fadlilah, Alif Nurul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine the effectiveness of group counseling services through group discussion techniques in enhancing adolescents’ emotional regulation skills. The research employed a pre-experimental approach using a one-group pretest-posttest design. The sample consisted of 10 students selected purposively based on a high need for emotional management. The instrument used was an emotional regulation questionnaire that had been tested for validity and reliability. Data were analyzed using paired sample t-test to determine the difference between pretest and posttest scores. The results showed an increase in the average score from 59.80 to 75.40 after the intervention. The t-test indicated a significance value of 0.000 0.05, confirming a significant difference before and after the service. These findings suggest that group discussion techniques within group counseling are effective in significantly improving adolescents’ emotional regulation abilities.